Сергей Параджанов в контексте украинского поэтического кинематографа - Чепалов, Александр (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Рассматриваются ключевые аспекты влияния С. Параджанова на развитие украинского поэтического кинематографа, вывeдшие его на международный уровень. Показано, что фильмы Параджанова и его нереализованные сценарии представляют собой целостный и не до конца исследованный художественный мир Мастера. Դիտարկվում են Ս. Փարաջանովի՝ ուկրաինական պոետիկ կինեմատոգրաֆի վրա ունեցած ազդեցության առանցքային կողմերը, որոնք ռեժիսորին հանել են միջազգային ասպարեզ։ Ցույց է տրվում, որ Փարաջանովի ֆիլմերը և չիրականացված սցենարներն իրենցից ներկայացնում են ամբողջական, ոչ լիարժեքորեն հետազոտված գեղարվեստական աշխարհ։ The article examines the key aspects of Sergey Parajanov’s influence on the development of Ukrainian poetic cinema, which advanced him to the international level. It is shown that Parajanov’s films and his unproduced screenplays represent a holistic artistic world of a Master, waiting to be fully explored. His impact on the development of Ukrainian national self-consciousness is noted.
Keywords: Искусствоведение; Кинематография